Worldwide child and adolescent mental health begins with awareness: A preliminary assessment in nine countries - Hoven, Christina W.; Doan, Thao; Musa, George J.; Jaliashvili, Tea; Duarte, Cristiane S.; Ovuga, Emilio; Ismayilov, Fuad; Rohde, Luis A.; Dmitrieva, Tatjana; Du, Yasong; Yeghiyan, Maruke; Seif El Din, Amira; et al. (International Review of Psychiatry, 2008)
To temper untoward mental health outcomes in children and adolescents, the World Psychiatric Association’s Presidential Global Child Mental Health Programme, in collaboration with the WHO and the International Association of Child and Adolescent Psychiatry and Allied Professionals, established a Child Mental Health Awareness Task Force headed by Sam Tyano. Its task was to develop methodologies to increase awareness among policy-makers, community leaders, health professionals, teachers, parents, and children. Based on a prior comprehensive international search for effective techniques for information dissemination, an awareness manual was written for use by health professionals in diverse communities so as to guide the design and implementation of location specific awareness campaigns. We assessed the children, parents and teachers both before and after the campaign to determine changes in knowledge, attitudes and understanding of mental health. The school-based studies were conducted in selected communities in nine countries on five different continents distinguished by their different languages, cultures and their differing levels of economic development: Armenia, Azerbaijan, Brazil, China, Egypt, Georgia, Israel, Russia, and Uganda. In the six sites that completed all assessments, indicators of positive change in awareness of child mental health were identified, and results demonstrated an increased willingness to discuss emotional problems freely. These data support the utility of collaborating with schools so as to foster better child mental health in such under-resourced communities.
Keywords: Worldwide child; Adolescent mental health; Preliminary assessment